O acompanhamento de egressos como ferramenta de inserção no mercado de trabalho do ponto de vista do setor de estágio e emprego do sistema CEFET/RJ - Guimarães, Maria Angelica Miranda (2013)
This research proposes the deployment of a generic model of tracking graduates trained, more specifically, the technical courses of educational institution, so that meets companies seeking manpower from these institutions. The interaction, relative sought in School-Company, is a prerequisite for the teaching will match the reality of the market, providing a constant interchange between them factor. To this end, the method adopted in this study was based on analysis of the conditions for monitoring the graduating students by a public educational institution ( CEFET/RJ ) and application of a field survey of graduating students, companies and technical and administrative staff. Were used as data collection instruments, structured questionnaires, with intent to comply with the paucity of the degree that the institution meets the demands of the labor market and, finally, uses such important and essential information in the formulation of the proposed model with the strategies combined institutional and educational